The effect of ambient air temperature on cardiovascular and respiratory mortality in Thessaloniki, Greece - Kouis, Panayiotis; Kakkoura, Maria; Ziogas, Konstantinos; Paschalidou, Anastasia K.; Papatheodorou, Stefania (My University, 2019)
Objectives: There is a growing body of evidence linking ambient air temperature and adverse health effects, in the form of hospitalization or even increased mortality mainly due to respiratory and cardio/cerebro-vascular illnesses. In the present study, we examine the association between high ambient air temperature and cardiovascular as well as respiratory mortality for the population of the greater area of Thessaloniki, Greece, taking into account the role of particulate pollution as a potential confounder. Methods: A mixed Poisson regression model, using a quasi-likelihood function to account for potential over-dispersion in the outcome distribution given covariates, was combined with distributed lag non-linear models, to estimate the non-linear and lag patterns in the association between mortality and daily mean temperature from 1999 to 2012. Results: A direct heat effect was found, as the mortality risk increased sharply above the temperature threshold of 33 °C, suggesting a significant effect of high temperatures on mortality on the same and next day of the heat events (lags 0–1) which was retained for a week, whereas a harvesting effect was noticed for the following days. Cardiovascular and respiratory mortality risk increased by 4.4% (95% CI 2.7%–6.1%) and 5.9% (95% CI 1.8%–10.3%) respectively on the same and following day of a heat event, whereas the risk dropped steeply in the following days. Particulate matter did not confound the association between high temperature and mortality in this population. Conclusion: There is a significant association between mortality and hot temperatures in Thessaloniki, Greece. Reduction in exposure to increased temperatures, as part of prevention measures and strategies, should be considered for vulnerable subpopulations.
Keywords: Heat mortality; Cardiovascular mortality; Respiratory mortality; Time series; Particulate matter